2021
DOI: 10.1177/17496020211044821
|View full text |Cite
|
Sign up to set email alerts
|

Youthification of television through online media: Production strategies and narrative choices in DRUCK/SKAM Germany

Abstract: This article discusses online media’s contribution to the youthification of television through the case study of DRUCK (tr. Pressure, 2018–), the German format adaptation of SKAM (tr. Shame, 2015–17). Youthification is understood as the television industry’s attempts to reach and win back teen and tween viewers with strategies in production, representations, aesthetics and distribution. In DRUCK, online media are integral to the youthification in all these strategies. Our multifaceted analysis of this serial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Youth and tween viewers are a 'desperately sought audience' (Krauß & Stock, 2021). With their online expansions, many well-known commercial and public service broadcasters have turned to teen audiences.…”
Section: Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Youth and tween viewers are a 'desperately sought audience' (Krauß & Stock, 2021). With their online expansions, many well-known commercial and public service broadcasters have turned to teen audiences.…”
Section: Contentmentioning
confidence: 99%
“…The streaming media platform is also like a movie library that incorporates as many movies as possible into its database, so that different users can find content that suits their own tastes on the streaming media platform, thereby expanding the user base, and there is also content for specific young people. Krauß & Stock (2021) discusses how the youthification appears through online media in production strategies and narrative choices. The phrase "youthification" describes efforts made by professionals to engage and retain youth, whose media consumption is dominated by digital and international media platforms (Sundet, 2021;Sundet & Lüders, 2023).…”
Section: Contentmentioning
confidence: 99%
“…2.See for example Krauß and Stock (2021), Redvall and Christensen (2021), Steemers (2022), Sundet (2021a), Sundet (2021b).…”
mentioning
confidence: 99%
“…Past research found that, for the same sustainable action that television industry engages in, different beliefs about adoption to technology might result in different consumer responses especially in the Internet-distributed television services (Krauß & Stock, 2020;Wayne, 2022;Wayne & Uribe Sandoval, 2021). The perceived underlying motive of adoption of television industry to digital media is an important factor that generates awareness to online media (Kelly, 2019;Krauß & Stock, 2021;Rodwell, 2021). In particular, substitutability of the media is one of those conditions under which viewership engagement may swaying electronic media to online video content and production (Fung, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although TV industry business models, in general, have been conceptualized as getting advertising on TV, social media presence is a way to draw broader updated audience (Lahey, 2016). For this perspective, a TV business model aiming for advertising to be sustainable needs to engage with bigger audiences in different platform to negotiate and make sense of social media presence (González-Neira et al, 2021;Johnson, 2020;Jones-Edman et al, 2019;Krauß & Stock, 2021). Organizing quantity of videos in the channel through enough database of snippet of TV programs is critical for sustainable YouTube presence to fulfill the promise of social media interaction that answer the reason why industry utilize YouTube as the marketing communication platform (Yang et al, 2012).…”
Section: Quantitymentioning
confidence: 99%